Sistem Informasi Pemantauan Lalu Lintas Jaringan pada Penyedia Layanan Internet (ISP) PT. AcehLink Media - Ahmad, Adi; Alfina; Nafrial, Eli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Information systems have become a crucial part of various institutions and modern societies today. With the availability of appropriate information systems, many benefits can be gained, ultimately enhancing work productivity. To maintain the stability and availability of information networks, a well-managed system is required, one that can address any arising issues. Monitoring network devices is essential to assist network administrators in observing and controlling the installed network systems. PT. AcehLink Media, located at Jalan Pocut Baren No. 31A, Gampong Keuramat, Kuta Alam District, Banda Aceh City, is an Internet Service Provider (ISP) company that serves Internet users, particularly in the Banda Aceh area, 24 hours a day. The network device monitoring system currently implemented at PT. AcehLink Media relies on a manual method using ping from Command Prompt. As an Internet service provider, this method is understandably ineffective, especially when network issues occur. The methodology used in this research includes Data Collection Methods derived from Literature Studies and Field Observations (including Interviews), as well as System Analysis and Design Methods. The system to be designed is based on the Simple Network Management Protocol (SNMP) using the CACTI application. CACTI is a frontend application of the Round Robin Database Tool (RRDTool), which stores information in a MySQL database and generates graphs based on that information. The implementation of the designed Network Device Monitoring Information System is expected to assist personnel in troubleshooting network issues when they arise, thus ensuring the stability of Internet services for all customers.